Analisis Pengaruh Banjir Rob Terhadap Kualitas Air Tanah Di Kawasan Pesisir Selatan Puger Kabupaten Jember - Musarofa, Musarofa; Yuvita Dian , Siswanti; A Rosyid, Latifa Mirzatika (Indonesian Journal Publisher, 2024)
The potential benefits of a beach for the surrounding community are numerous, including increasing the tourism sector and supporting the economy of local residents. Apart from this potential, there is also the potential for disasters, one of which is ROB flooding. Recently there was a tidal flood that hit the southern coast, causing seawater to enter residential areas and damage various public facilities in the Puger coastal area. The aim of this research is to identify the influence of tidal floods that occurred in the southern coastal area of ​​Puger, on groundwater quality, in terms of water quality in accordance with the quality standards of Minister of Health Regulation No. 2 of 2023 concerning Implementing Regulations of Government Regulation Number 66 of 2014 concerning Environmental Health. The method used is descriptive qualitative conservation data and sampling at three locations by conducting laboratory tests. From this research, it can be concluded that there is a decline in the quality of groundwater in the affected area which includes three observation locations. Where the TDS parameter is still below the quality standard of <300 mg/L, while for salinity and e-coli each has a value greater than the established quality standard. In this study, both parameters had <0% with values ​​for sampling 1 (2 per cent) sampling 2 (0.9 per cent) and sampling 3 (0.5 per cent ), for salinity and <0 CFU/100ml for e-coli content with values ​​for sampling 1 (50 CFU/100ml), sampling 2 (70 CFU/100ml) and sampling 3 (100 CFU/100ml). The ROB floods that occur in coastal areas result in the quality of groundwater becoming polluted and it must be treated first before it can be used by local communities.